Synthesis of ABC miktoarm star copolymers via organocatalyzed living radical polymerization - Ge, Yicen (2020)
ABC-type miktoarm star copolymers are synthesized using a single living radical polymerization (organocatalyzed living radical polymerization) via a "combinatorial" approach. The arm A is poly(butyl acrylate), the arm B is poly(methyl methacrylate), and the arm C encompasses hydrophobic and hydrophilic polyacrylates. A poly(butyl acrylate) with a vinyl chain end (macromonomer) is synthesized. A poly(methyl methacrylate) is subsequently connected to the reactive vinyl group to generate diblock copolymer. From the junction of the diblock copolymer, polymer C grew to yield star copolymers. An amphiphilic star copolymer is also synthesized, and its self-assembly structure is studied in an aqueous solution.